The extent to which Islamic education courses at the secondary level incorporate the dimensions of intellectual security in the Kingdom of Saudi Arabia - Al- Shahrani, Mesfer Saad Mesfer (Journal of Educational and Psychological Sciences, 2022)
The objective of the research is to know the extent to which Islamic education courses include the following dimensions of intellectual security: Religious dimension, national dimension, social dimension, after dialogue and acceptance of opinions, after positive thinking (critical thinking), and to achieve this goal the researcher used the descriptive approach based on the method of content analysis, the researcher also designed the study tool that consisted of the content analysis card, the research sample was determined in the book Hadith 1 course for high school students (curriculum system) in to: there is a disparity in the degree of inclusion of dimensions of intellectual security in the course of Hadith 1 for high school students, where it came in the following order: in the first degree the religious dimension by the percentage of repetitions reached (13,002%) to the total content of the course, in the second degree the social dimension by the percentage of repetitions reached (10%) to the total content of the course, in the third degree the national dimension by the percentage of repetitions reached (5%) to the total content of the course, in the fourth: Review the content planning of Hadith course 1 for high school students (courses system), in a way that allows in achieving parity and balance between the depth of content and its organization, in including the dimensions of intellectual security and distribution in an appropriate manner among its subjects, in addition to including the activities of the content of the course on the dimensions of intellectual security.
Keywords: extent of inclusion; Islamic education courses; dimensions of intellectual security; secondary level